Undoing Islamophobia: Awareness of Orientalism in Social Work. Issue 2 (4th May 2017) - Beck, Elizabeth; Charania, Moon; Abed-Rabo Al-Issa, Ferdoos; Wahab, Stéphanie
ABSTRACT: Islamophobia describes the racism, exploitation, and violence experienced by Arabs, individuals of Arab descent, and Muslims. Although social workers are meant to challenge social injustice, social work codes of ethics and the literature are without guidance for unlearning Islamophobia. Arguing that one's ability to interrupt Islamophobia is strengthened by an understanding of the historical record and theoretical tenets of Orientalism, we offer social workers explicit linkages between Orientalism and Islamophobia and engage with the idea of Islamo-racism. In this article, we attend to the ways in which Orientalism is used to "other" individuals while strengthening white hegemony, and we link those processes with Islamophobia and Islamo-racism. We conclude with some strategies derived from postcolonial theory to disrupt Islamophobia.